Correlates of active commuting to school among portuguese adolescents: An ecological model approach - Grao-Cruces, Alberto (2022)
Active commuting to and from school can be an important contribution to improving health in adolescents. This study aimed to analyze the influence of multilevel variables of the ecological model in the active commuting of a representative sample of Portuguese adolescents. The 2018 Health Behaviour in School-Aged Children questionnaire was applied to 5695 adolescents with an average age of 15.5 years old (SD ± 1.8), 53.9% of whom were girls. The associations were studied by applying chi-square tests and multivariate logistic regression models. In this study, 36.5% of the participants reported walking or cycling to school. Active commuting to school was directly associated with age (OR = 1.2; p < 0.05), strong family support (OR = 1.2; p < 0.05), a moderate to low financial level of the family (OR = 1.3; p < 0.05) and living near the school (OR = 2.4; p < 0.05). The results revealed that an adolescent's choice to travel to and from school using an active mode of transportation increased with strong family support. As a result, promotion campaigns should consider the adolescent's family context.